2014
DOI: 10.1007/s11144-014-0753-8
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical study of the hetero Diels–Alder reactions between (E)-2-aryl-1-cyano-1-nitroethenes and ethyl vinyl ether: one-step or zwitterionic, two-step mechanism?

Abstract: The mechanistic aspects of the hetero Diels-Alder reactions between strongly electrophilic (E)-2-aryl-1-cyano-1-nitroethenes and ethyl vinyl ether have been analyzed on the basis of kinetic experimental results as well as quantum chemical simulations of reaction paths. These reactions may theoretically proceed via one step or stepwise, zwitterionic mechanism. It was found that the conversion of addends into adducts carried out via polar, but not zwitterionic mechanism. This is confirmed by kinetic substituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…They are useful compounds applied, e.g. in syntheses of many four-, fiveand six-membered compounds in cycloaddition reactions [6][7][8][9][10][11]. Applications of nitroalkenes in organic synthesis are largely due to their ease of conversion into a variety of functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…They are useful compounds applied, e.g. in syntheses of many four-, fiveand six-membered compounds in cycloaddition reactions [6][7][8][9][10][11]. Applications of nitroalkenes in organic synthesis are largely due to their ease of conversion into a variety of functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The stationary points on reaction paths were localized in an analogous manner as in the case of the previously analyzed DA reaction of conjugated nitroalkenes with alkyl-vinyl ethers [29,30]. In particular, for the structure optimization of the reactants and the reaction products, the Berny algorithm [31] was applied.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The yields of nitronates (45a-d) were very high (75-90%) but a mixture of diastereoisomers was obtained (Table 12). The kinetic aspects of these transformations have also been recently discovered [9] In the same year, Pizzo et al [3] showed an example of intramolecular cycloaddition in 2-(2' -(3",3"-dimethyl)allyloxyphenyl)-1-cyano-1-nitroetene (46) generated in situ. This reaction led to the formation of cis-4a,10b,-dihydro- 1-cyano-4,4,dimethylbenzo[b]pyrene- [4,3-d] [1,2] oxazine-2-oxide (47) and its 4a-epimer (48) in a 16:1 ratio and with a 60% yield of (48).…”
Section: [2+4] Cycloaddition Reactions With 2-aryl-1-cyano-1-nitroethmentioning
confidence: 96%
“…The chemical transformations of these compounds include [2+3] cycloaddition to nitrogen-containing Three-Atoms-Components (TACs), which occupies an important place among the synthetic tools of organic chemistry [7]. Several examples of the participation of ACNs in Diels-Alder reactions as ethylenes as well as heterodienes are also known [3,8,9]. This paper is a continuation of our study on the chemistry of 2-aryl-1-cyano-1-nitroethenes.…”
Section: Introductionmentioning
confidence: 99%